Orthogonal preserving quadratic stochastic operators: Infinite dimensional case - Mukhamedov, Farrukh; Embong, Ahmad Fadillah; Pah, Chin Hee (IOP Publishing, 2017)
In the present paper, we consider orthogonal preserving quadratic stochastic operators defined on infinite dimensional simplex. We provide a full descriptions of such kind of operators. Moreover, certain examples are given.